Le paysage politique pour territorialiser l’action publique et les projets de développement : le cas de l’éolien au Québec - Marie-José Fortin; Anne-Sophie Devanne; Sophie Le Floch (Développement Durable et Territoires)
Industries and large infrastructures have been seen as a source of development for decades. This idea is although put into test by opponents of such projects. This paper is looking at conflicts raising around wind farms’ projects in eastern Canada. First, we will describe the settlement of this renewable energy in the province of Quebec, trough four phases. By doing so, we try to demonstrate that the conflicts gave rise to new planning practices supported by public authorities. We shall underline changes noticeable in regard of more classic practices in landscape domain. We will then discuss the questions that still remain concerning experts knowledge and governance practices. To conclude, we will underline how research investing political dimensions of landscape combined to regional studies could offer an understanding of relationships between modern societies and productive activities.